An Instruments to Accelate Development of the Klambir Lima Tourism Village with the Regional Existence Study Method - Milanie, Feby; Aryza, Solly; Sitepu, Sukma Aditya; Syahfitri, Elvira Seftiani (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The village area of Kelambir 5 has so far been considered to have received less attention so several activities are needed to support the economy of the surrounding community and activities that can provide a pleasant and healthy increase because they can only be passed by cycling or walking. These activities depend on the interest of the community and tourists in choosing a tour. This study is intended to contribute to the analysis of destinations in one of the important destinations in the North Sumatra area. This study of heritage trail tourism objects in Kotagede uses qualitative methods coupled with the use of high-resolution remote sensing image data in a more interactive visualization of results. I want to make it show the tourist attractions in kelambirlima. The tour packages are managed in a participatory manner by the surrounding community and can still develop for the better if they get direct attention from the government and stakeholders who are interested in managing the tourism area in the village of kelambirlima.